Fracture toughness determination of fused silica by cube corner indentation cracking and pillar splitting. (15th January 2020) - Bruns, Sebastian; Petho, Laszlo; Minnert, Christian; Michler, Johann; Durst, Karsten
Abstract: In this paper the applicability of the pillar splitting technique for fracture toughness determination on anomalous behaving bulk fused silica glass is explored. The results are compared to conventional cube corner indentation cracking analyzed using the Lawn, Evans and Marshall model (JACerS, 63 (1980) 574). The experimental analysis is supported by constitutive Finite Element Analysis with cohesive zones to determine adequate gauge factors to correlate the load instability upon splitting to the fracture toughness Kc. The role of densification on pillar splitting was critically examined. The results show a fragmentation of the micro pillar into three parts, a failure pattern as proposed by Sebastiani et al. (Philos. Mag., 95 (2014) 1928). Therefore, the applicability of pillar splitting to (anomalous) glasses is confirmed. Cohesive zone FEA delivered the gauge factors required for fracture toughness calculation. The influence of densification on those factors, however, was found to be small for indentation cracking and negligible for pillar splitting. With the corresponding set of gauge factors fracture toughness values in good accordance with literature could be determined. Inside the SEM, moreover, electron beam irradiation has been found to enhance the fracture properties of fused silica. Graphical abstract: Image 1 Highlights: The pillar splitting technique is applicable to anomalous behaving glasses. Densification plays a minor role in indentation cracking and is negligible for pillar splitting. Indentation cracking and pillar splitting deliver similar fracture toughness values. Electron beam irradiation affects experiments inside the SEM.